THE ANALYSIS OF THE FOREIGN LEGISLATION IN MATTERS OF LIABILITY FOR CERTAIN TYPES OF CRIMINAL OFFENSES AGAINST THE PERSON - Bauyrzhan Nuralyuly Бейсеналиев (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
This article analyzes the foreign legislation in matters of liability for certain types of criminal offenses against the person. The author analyzes the different compositions, and the definition of crimes against the person, and make constructive suggestions for improvement of the Criminal Code of the Republic of Kazakhstan